University Students' Perception of Duolingo to Improve Vocabulary Mastery in Learning English - Cahyoningtyas, Azizah Palupi (Journal of English Language and Education, 2024)
Mastering vocabulary in learning English as a foreign language often poses challenges for students, as they must memorize and apply words in new contexts, unlike their native language, which is acquired naturally. In recent years, web-based games and educational applications have gained popularity by creating enjoyable learning environments that reduce student anxiety and facilitate vocabulary acquisition, one example being Duolingo. This study aims to explore students' perceptions of using Duolingo to enhance their English vocabulary. The research adopts a mixed-method approach with purposive sampling. Findings reveal that students have a positive perception of the effectiveness of Duolingo in enriching their English vocabulary. The majority of participants agreed that the interactive game-based learning approach makes the learning process more enjoyable and engaging. Many students appreciated the flexibility of the application, allowing them to learn anytime and anywhere, which is an added value in helping them retain vocabulary effectively.